Cost recovery strategies for public sector Botanic Gardens - Wong, Wei Har (2008)
This study is a comparative case study of two botanic gardens, Singapore Botanic Gardens and Fairchild Tropical Garden in Miami, Florida, United States of America, complemented by quantitative tests conducted on other botanic gardens. Based on prevailing literature and existing models, this study identifies four critical “cost recovery” strategies or factors.